UTILIZING EXPERIMENTAL COMBINATION DESIGN: OPTIMIZATION OF FOOD BAR RECIPE BASED ON PURPLE SWEET POTATO - Tri Dewanti Widyaningsih; Kiki Fibrianto; Trifena Honestin; Sigalingging, Catherine Novita Sari (Fakultas Teknologi Pertanian Universitas Brawijaya, 2023)
Modern food technology can create nutritious goods that are useful and simple to consume. Food bars are convenient, calorie-dense, and healthy items. It is usually made from a variety of culinary ingredients combined and then molded into a sturdy, handy product. The goal of this study is to create a food bar using a blend of dried strawberries (DS), moringa flour (MF), mung bean flour (MBF), and purple sweet potato paste (PSPP). The formulation of DS, MBF, MF, and PSPP was improved by utilizing a mixture design of experiments with Minitab software. The predicted outcomes of this formulation are maximal antioxidant activity, maximum total flavonoids, and maximum total phenolic. Using 54.84% purple sweet potato paste (PSPP), 6.21% moringa flour (MF), 33.95% mung bean flour (MBF), and 5.00% dried strawberries (DS) allowed for an ideal maximal antioxidant activity. The antioxidant activity was 16.44 mg TE/g; the total flavonoid was 11.35 mg QE/g; and the total phenolic was 10.70 mg GAE/g.